Analisis Tingkat Keramahan Lingkungan Alat Tangkap Pancing Ulur di Perairan Pantai Tenau Kupang Nusa Tenggara Timur - Sapitri, Junita Indah; Noor Tajuddin; Saraswati Exist (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2026)
The fisheries sector plays an important role in Indonesia’s economy due to its abundant marine resources; however, unsustainable fishing activities have caused damage to marine ecosystems and a decline in biodiversity. To support sustainable fisheries management, the use of environmentally friendly fishing gear is essential. At the Tenau Coastal Fishing Port (PPP Tenau) in Kupang, East Nusa Tenggara, handline fishing is the most commonly used traditional fishing method among small-scale fishers because it is selective and causes minimal habitat disturbance. This study aims to analyze the environmental friendliness level of handline fishing gear based on the nine criteria of the Code of Conduct for Responsible Fisheries (CCRF) established by FAO in 1995, which include gear selectivity, habitat impact, fisher safety, catch quality, product safety, by- catch, biodiversity impact, capture of protected species, and social acceptance. The research was conducted from November 2025 to January 2026 using a descriptive quantitative method involving 30 handline fishermen selected from a population of 420 using the Slovin formula with a 20% error rate. Data were collected through observation, interviews, and documentation, then analyzed using a weighting system based on the guidelines of the Ministry of Marine Affairs and Fisheries (2006). The results are expected to show that handline fishing is categorized as environmentally friendly to highly environmentally friendly and can serve as a basis for developing sustainable fisheries management policies in East Nusa Tenggara.